Comprehensive laboratory measurements resolving the LMM dielectronic recombination satellite lines in Ne-like Fe xvii ions - Grilo, Filipe; Shah, Chintan; Kühn, Steffen; Steinbrügge, René; Fujii, Keisuke; Marques, José; Gu, Ming Feng; Santos, José Paulo; Crespo López-Urrutia, José Ramon; Amaro, Pedro (The astrophysical journal, 2021)
We investigated experimentally and theoretically dielectronic recombination (DR) populating doubly excited configurations (LMM) in Fe xvii, the strongest channel for soft X-ray line formation in this ubiquitous species. We used two different electron beam ion traps and two complementary measurement schemes for preparing the Fe xvii samples and evaluating their purity, observing negligible contamination effects. This allowed us to diagnose the electron density in both EBITs. We compared our experimental resonant energies and strengths with those of previous independent work at a storage ring as well as those of configuration interaction, multiconfiguration Dirac-Fock calculations, and many-body perturbation theory. This last approach showed outstanding predictive power in the comparison with the combined independent experimental results. From these we also inferred DR rate coefficients, unveiling discrepancies from those compiled in the OPEN-ADAS and AtomDB databases.